Standards of ultrasound imaging of the adrenal glands - Rafał Z. Słapa; Wiesław S. Jakubowski; Katarzyna Dobruch-Sobczak; Anna A. Kasperlik-Załuska (Journal of Ultrasonography, 2015)
Adrenal glands are paired endocrine glands located over the upper renal poles. Adrenal pathologies have various clinical presentations. They can coexist with the hyperfunction of individual cortical zones or the medulla, insuffi ciency of the adrenal cortex or retained normal hormonal function. The most common adrenal masses are tumors incidentally detected in imaging examinations (ultrasound, tomography, magnetic resonance imaging), referred to as incidentalomas. They include a range of histopathological entities but cortical adenomas without hormonal hyperfunction are the most common. Each abdominal ultrasound scan of a child or adult should include the assessment of the suprarenal areas. If a previously non-reported, incidental solid focal lesion exceeding 1 cm (incidentaloma) is detected in the suprarenal area, computed tomography or magnetic resonance imaging should be conducted to confi rm its presence and for differentiation and the tumor functional status should be determined. Ultrasound imaging is also used to monitor adrenal incidentaloma that is not eligible for a surgery. The paper presents recommendations concerning the performance and assessment of ultrasound examinations of the adrenal glands and their pathological lesions. The article includes new ultrasound techniques, such as tissue harmonic imaging, spatial compound imaging, three-dimensional ultrasound, elastography, contrast-enhanced ultrasound and parametric imaging. The guidelines presented above are consistent with the recommendations of the Polish Ultrasound Society.